Telaah Pesan Kampanye #Bijakkelolasampah pada Instagram @Waste4Change Mengenai Program Send Your Waste yang Berdampak Terhadap Sikap Followers Mengelola Sampah Skincare - Galuh Dinda Utami; Syafril Tahar; Rustono Farady Marta; Natasia Angreani; Rizki Briandana (JCommsci - Journal Of Media and Communication Science, 2022)
The study aims to identify how the campaign message of #Bijakkelolasampah at Instagram @Waste4Change affects their followers regarding Send Your Waste program. The study results implicate that the followers of @Waste4Change followers, which consists of 21-25 years of age and female-oriented respondents, fulfill the validity and reliability tests with a score of 0.30. The mean of the campaign message has a score of 3.43, which is within a “very good” interval category. The regression analysis also confirms that the campaign messages of @Waste4Change have a correlation score of 0.806 among their followers. This means the message of #Bijakkelolasampah campaign has around 65% affinity, whereas the other 35% is affected by other means. The @Waste4Change Instagram managers should pay more attention to every upload so as not to create an ambiguous meaning for their followers.